KEEFEKTIFAN MODEL KOOPERATIF TIPE THINK TALK WRITE PADA ASPEK KETERAMPILAN MEMBACA MATERI BAHASA INDONESIA SISWA KELAS III DI SD - Bunga Wulan Dani, Vinorika; Sulianto, Joko; Patonah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
. This research is motivated by the low skills of reading, comprehension and reading aloud of narrative texts in the Indonesian language subject, third grade students of SD Negeri Pandean Lamper 02 Semarang. The learning process that tends to be teacher-centered makes students less active in constructing thoughts and understanding the intrinsic elements of the story in depth. The quantitative research using the Quasi Experiment method with the One Group Pretest-Posttest design aims to test the effectiveness of the Think Talk Write (TTW) type cooperative learning model on improving students' reading skills. The sample population as well as the study involved all grade III students as many as 23 respondents who were taken through saturated sampling techniques. Data collection instruments are oral tests and written tests that have been tested for validity and reliability (). Data analysis using the Paired Sample T-Test showed a significance value (2-tailed) of 0.000 (< 0.05) and a mean differential value of -2.34783, which means that the Posttest value increased significantly compared to the pretest. In addition, the results of the N-Gain Score test showed a mean value of 0.8211 (82.11%), which is included in the High category with an effective effectiveness level. The conclusion of the study proves that the Think Talk Write (TTW) model is scientifically effective in improving students' narrative text reading skills.